Enhancement of titanium dioxide (TiO2) dye-sensitized solar cells (DSSCs) performance with incorporation of reduced graphene oxide (rGO) - Talib, Azman (2022)
The purpose of this thesis is to investigate the structural, optical and electrical properties of titanium dioxide (TiO2) dye-sensitized solar cells (DSSCs) with the incorporation of reduced graphene oxide (rGO). In this experiment, rGO from electrochemical exfoliation, was deposited onto few fluorine-doped tin-oxide (FTO) substrat through spray pyrolysis deposition (SPD) method with different rGO volumes. Then, all the fabricated FTOs went through rutile-phase TiO2 (r-TiO2) with hydrothermal synthesis. From DSSCs analysis, 0.50 mL of rGO volume exhibited the best photovoltaic (PV) performance with the efficiency of 2.61% and open-circuit voltage of 0.70 V. The successful synthesis of rGO, incorporated with TiO2 was confirmed using Raman spectroscopy. The analysis of the samples was done using X-ray diffraction, field emission scanning electron microscopy, ultraviolet-visible spectrophotometry, and incident photon-to-carrier conversion efficiency spectra. Then, another rGO which was produced through Hummers method, was incorporated into anatase-phase TiO2 (a-TiO2) as nanocomposite (NC) mixture. After that, through SPD method, the NC mixture was deposited onto few FTOs. The a-TiO2 was produced by adding TKC-302 into TiO2 P25 powder. The NC mixture samples significantly contributed towards the improvement of efficiency, when compared with samples without rGO. When 2 mL of rGO was added into a-TiO2, PV performance achieved the highest efficiency of 3.15% and current density of 5.98 mA/cm2. Finally, the combination of rGO and a-TiO2 NC mixture, was overlayered onto r-TiO2. The 2 mL of rGO/a-TiO2 NC mixture which was deposited through SPD onto r-TiO2, exhibited the best PV performance with the highest efficiency of 5.72% and the current density of 10.37 mA/cm2. The rGO acted as an important material, to maximise the photogenerated electrons of photo-induced charge carriers. The photogenerated electrons from dyes transferred through r-TiO2, effectively traveled out to the circuit load, which underwent recombination with holes in the solar cells with enhancement of rGO functions.